Fabrication of a composite modified glassy carbon electrode: a highly selective, sensitive and rapid electrochemical sensor for silver ion detection in river water samples - Syaza Azahari; Palanivel Sathishkumar; Rahmalan Ahamad; Farediah Ahmad; Abdull Rahim Mohd Yusoff (The Royal Society of Chemistry, 2024)
Issue 28